2022
DOI: 10.1145/3479431
|View full text |Cite
|
Sign up to set email alerts
|

Can Computing Be Diversified on “Principles” Alone? Exploring the Role of AP Computer Science Courses in Students’ Major and Career Intentions

Abstract: The Advanced Placement Computer Science Principles (APCSP) course was introduced in 2016 to address long-standing gender and racial/ethnic disparities in the United States among students taking Advanced Placement Computer Science (APCS) in high school, as well as among those who pursued computing majors in college. Although APCSP has drawn a more diverse population of course takers than the traditional Advanced Placement Computer Science A (APCSA) course, questions remain about whether the new course portends … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…For example, Brown and Brown (2020) found that females who participated in the AP CS Principles program were more motivated to take the AP CS A exam and likely to go to college when compared to students who didn’t participate in the AP CS Principles programs. Similarly, Sax et al (2022) found positive associations between participation in AP programs and majoring in computing fields for girls. In another study, Boda and McGee (2021) found that students who enrolled in early CS programs increased girls’ participation in AP CS programs.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…For example, Brown and Brown (2020) found that females who participated in the AP CS Principles program were more motivated to take the AP CS A exam and likely to go to college when compared to students who didn’t participate in the AP CS Principles programs. Similarly, Sax et al (2022) found positive associations between participation in AP programs and majoring in computing fields for girls. In another study, Boda and McGee (2021) found that students who enrolled in early CS programs increased girls’ participation in AP CS programs.…”
Section: Discussionmentioning
confidence: 85%
“…However, to the best knowledge of the authors, no current studies investigated the direction and magnitude of gender disparities in AP CS exams. Given that the AP CS program is a major pipeline for the computing workforce, such an investigation also helps to understand current and future directions of gender disparities in K–12 CS education and beyond (Sax et al, 2022).…”
Section: Present Studymentioning
confidence: 99%
See 2 more Smart Citations
“…This is because the goal of the CS was to determine whether respondents were satisfied with the path they were taking in their separate jobs. (Sax et al, 2022). People who have high CS scores are not only able to demonstrate that they are capable of experiencing positive emotions, but they also demonstrate that they are content with the career path that they have chosen for themselves.…”
Section: Resultsmentioning
confidence: 99%